Global trends and research status in clonal hematopoiesis: a bibliometric analysis of the last 10 years - QingQing Luo; Li Yu (Discover Oncology)
Abstract Objective Clonal hematopoiesis (CH) refers to the clonal expansion of hematopoietic stem cells caused by somatic mutations. CH is commonly observed in elderly individuals and is closely associated with myeloid malignancies as well as various non-malignant diseases. This study aims to explore the research trends and hotspots of CH using bibliometric analysis. Methods Relevant studies were retrieved from the Web of Science Core Collection database based on predefined inclusion criteria. Bibliometric analysis and visualization were conducted using VOSviewer, CiteSpace, and R software. Results A total of 851 studies were included. From 2014 to 2024, the annual number of publications showed a consistent upward trend. The United States was identified as the leading country in this field, contributing 53.7% of the total publications. Harvard Medical School and Benjamin L Ebert were recognized as the most influential institution and author, respectively. Blood was the most prolific journal, with the highest citation and H-index. Research on CH-related gene mutations and their association with the risk of acute myeloid leukemia is currently the most extensively studied area, while cardiovascular diseases and inflammation have emerged as recent research hotspots. Conclusion This study is the first to systematically analyze research related to CH using bibliometric methods. Our analysis reveals the overall landscape of CH research and identifies the most influential contributors in the field, including countries, institutions, authors, and journals. Moreover, we identify emerging research hotspots and key areas, highlighting potential avenues for exploration and innovation within the field of CH.